2010
DOI: 10.1007/s00335-010-9305-3
|View full text |Cite
|
Sign up to set email alerts
|

The receptor locus for Escherichia coli F4ab/F4ac in the pig maps distal to the MUC4–LMLN region

Abstract: Enterotoxigenic Escherichia coli (ETEC) with fimbriae of the F4 family are one of the major causes of diarrhea and death among neonatal and young piglets. Bacteria use the F4 fimbriae to adhere to specific receptors expressed on the surface of the enterocytes. F4 fimbriae exist in three different antigenic variants, F4ab, F4ac, and F4ad, of which F4ac is the most common. Resistance to ETEC F4ab/F4ac adhesion in pigs has been shown to be inherited as an autosomal recessive trait. In previous studies the ETEC F4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 20 publications
2
28
0
Order By: Relevance
“…The low significant P -value of the Indel MUC13 marker (Table S2; Figure 5A) confirmed our previous results that MUC13 is not the causal gene for F4ab/ac ETEC susceptibility. Four markers of the Porcine SNP60 BeadChip (ALGA0072075 [GenBank:NC_010455.4; 144832256], ALGA0106330 (SNP3), DIAS0000584 [GenBank:NC_010455.4; 145414240] and MARC0006918 [unknown position]), and 2 additional markers ( MUC13 -226 [GenBank:NC_010455.4; 145,010,437] and MUC13 -813 [GenBank:NC_010455.4; 145,016,914]) were in complete LD with the F4ab/acR locus in a Swiss experimental herd [31]. Except for one sow and some of her offspring, markers ALGA0106330 (SNP 3), MUC13 -226 and MUC13 -813 were not in LD with the F4ab/acR locus [32].…”
Section: Discussionmentioning
confidence: 99%
“…The low significant P -value of the Indel MUC13 marker (Table S2; Figure 5A) confirmed our previous results that MUC13 is not the causal gene for F4ab/ac ETEC susceptibility. Four markers of the Porcine SNP60 BeadChip (ALGA0072075 [GenBank:NC_010455.4; 144832256], ALGA0106330 (SNP3), DIAS0000584 [GenBank:NC_010455.4; 145414240] and MARC0006918 [unknown position]), and 2 additional markers ( MUC13 -226 [GenBank:NC_010455.4; 145,010,437] and MUC13 -813 [GenBank:NC_010455.4; 145,016,914]) were in complete LD with the F4ab/acR locus in a Swiss experimental herd [31]. Except for one sow and some of her offspring, markers ALGA0106330 (SNP 3), MUC13 -226 and MUC13 -813 were not in LD with the F4ab/acR locus [32].…”
Section: Discussionmentioning
confidence: 99%
“…MUC4-mediated susceptibility was linked to the presence of high molecular weight glycoproteins (172). Based on linkage disequilibrium for MUC13 (173), and more specifically for six SNPs (two in MUC13) with the F4ab/ac receptor locus, this locus was located between the LMLN locus and microsatellite S0283 (174). Further studies confirmed a link between the F4ac receptor locus and MUC13, and pigs expressing at least one transcript predicted to encode a highly O-glycosylated MUC13 protein (MUC13B) were F4ac-susceptible, whereas pigs homozygous for the non-glycosylated allele (MUC13A) were F4ac resistant (175).…”
Section: Adhesins and Host Receptorsmentioning
confidence: 99%
“…MUC4 associates with the host receptor of enterotoxigenic Escherichia coli [6468]. Moreover, E. coli strains from phylogroup B2 harboring a pks+ island can produce a peptide-polyketide hybrid compound termed colibactin, which can trigger premature and transmissible senescence in mammalian cells, resulting in colon cancer [69].…”
Section: Changes In Muc4 Expression In Cancer Cellsmentioning
confidence: 99%